Growth and survival rate of vaname shrimp (Litopenaeus vannamei) at various doses of fertilizer - Abdul Rakhfid; Harlianti; Fendi; Karyawati (Sekolah Tinggi Ilmu Pertanian Wuna, 2017)
White shrimp (Litopenaeus vannamei) is considered able to replace black tiger shrimp (Penaeus monodon) as a positive diversification. Excellence shrimp vaname (L. vannamei) is a high nutritional value, fast growth and able to use the water column as a place to live so it can be maintained with high stocking density. Natural feed (phytoplankton) can be stimulated through fertilization. The study was carried out at the Ghonebalano Coastal Fish Seed Center (BBIP), aiming to determine the effect of using different doses of urea and TSP fertilizer on the growth and survival of vaname shrimp (L. vannamei). The study used a Completely Randomized Design with three levels of combination treatment of fertilizer doses, namely treatment A urea 0.5 g/TSP 0.7 g; treatment B Urea fertilizer dose 0.7 g/TSP 0.9 g and treatment C dose Urea fertilizer 0.9 g/TSP 1.11 g. The results showed that the highest growth was obtained in treatment B i.e. 1.54±0.16 g/individuals, compared with treatment A (1.11±0.08 g/individuals) and treatment C (1.32±0.10 g/individuals). Survival in treatment A was 71.11±3.85%, treatment B was 73.33±6.67% and treatment C was 75.55±3.85%. Analysis of variance at the 95% confidence level (α0.05) showed that the administration of urea and TSP fertilizers differed significantly (0.05>0.03) on growth, but did not significantly influence (0.05<0.58) on the survival of vaname shrimp larvae.